Potential of Lactoferrin Against the Radiation-Induced Brain Injury - Marina Yu. Kopaeva; Anton B. Cherepov; Irina B. Alchinova; Daria A. Shaposhnikova; Anna V. Rybakova; Alexandr P. Trashkov (Cells)
The purpose of this work was to study the effects of lactoferrin (Lf) on acute (days 3 and 15) and early-delayed (day 30) changes in the dentate gyrus of mouse hippocampus caused by whole-body gamma-irradiation. Male C57BL/6 mice received Lf (4 mg per mouse, i.p. injection) immediately after whole-body gamma-irradiation at a dose of 7.5 Gy from a 60Co source. The effect of Lf on mouse behavior was evaluated using “Open field” and “Elevated plus-maze” tests. The proportion of cells with DNA replication was determined by 5-ethynyl-2′-deoxyuridine incorporation (thymidine analog) and detected by a click reaction with azide Alexa Fluor 568. Lf treatment increased animal survival during the experiment (30 days), compensated for radiation-induced body weight loss, and prevented suppression of motor and exploratory activities. A pronounced anti-radiation effect of Lf on mouse brain cells has been demonstrated. A single injection of the protein allowed preserving 2-fold more proliferating cells and immature neurons in the dentate gyrus of the hippocampus of irradiated animals during the acute period of post-radiation injury development.